# 4(6y-9)+7

*print*Print*list*Cite

### 5 Answers

Simplify the expression: `4(6y-9)+7`

Use the distributive property:

`4(6y) - 4(9) + 7`

`24y - 36 + 7`

`24y-29`

**The simplified expression is 24y-29.**

QUESTION:-

4(6y-9)+7

SOLUTION:-

4(6y-9)+7

We are going to solve this equation by using BODMAS. Open the brackets and for that we will multiply 4 with both the values in the bracket,

24y-36+7

24y-29

It can not be simplified further. But we can also show the value of y;

24y-29=0

24y=29

y=29/24

Hence This can also be the answer.

Hence this problem is solved!

4 ( 6y - 9 ) + 7

In order to simplify this expression follow the rules of BODMAS / PEMDAS,

4 ( 6y - 9 ) + 7

Remove parenthesis by applying the distributive law i.e. multiplying both numbers inside the bracket by 4,

24y - 36 + 7

Add or subtract

**24y - 29 Answer.**

This is the most that it can be simplified.

4(6y-9)+7=0 is your equation

24y-36+7=0

24y-29 =0 move -29 to the other side by adding 29 to both sides then divide by 24

y=29/24

4(6y-9)+7

24y-36+7

24y-29

24y=29

y=29/24